The Impact of the Far Right on Mainstream Politics: Evidence from the Front National - Anthony Edo; Thomas Renault; Jérôme Valette (Institute of Labor Economics (IZA), 2025)
How does the electoral success of a far-right political force shape the strategies and policy platforms of mainstream candidates? We answer this question by exploiting the political shock of the creation of the Front National, an anti-immigration party, in 1972 and its sudden electoral breakthrough in the 1980s. Through a comprehensive textual analysis of candidate manifestos in French parliamentary elections from 1968 to 1997, we find that right-wing candidates respond to local far-right success, measured as voting shares, by amplifying the salience of immigration in their manifestos. They also adopt more negative positions on immigration and increasingly associate it with issues such as crime and the welfare state. In contrast, the ideological positions of left-wing candidates do not shift in response to far-right electoral gains. We finally show that the strategic adjustments of right- wing candidates help mitigate electoral losses to far-right competitors.
Keywords: F22; P16; D72; 330; political economy; anti-immigrant parties; electoral competition; party platform; immigration